Testing conditional superannuation as an anti-doping policy supplement for safeguarding athlete health and welfare - Lenten, L. J. A.; Smith, A. C. T. (Performance Enhancement & Health, 2020)
Given the significant, adverse health implications associated with performance-enhancing drugs in sport, anti-doping policy represents a pivotal intervention for not only protecting sport`s credibility, but also for safeguarding athletes` health. However, current World Anti-doping Agency (WADA) policy has proven limited in controlling banned doping. This letter reports on a pilot experimental economics study testing `conditional superannuation` as a novel anti-doping policy. A conditional superannuation policy compels athletes to direct a nominal percentage of their sport-related earnings into a managed fund, and only returned to athletes after a period of retirement. Results demonstrate that the policy outperforms existing penalties such as fines and bans. With sport`s hyper-competitive, commercial values, it remains improbable that an elite sports world will ever fully eliminate drugs. Nevertheless, sport needs regulation to help protect athletes from the health costs that arise from uncontrolled substance use. As existing penalty mechanisms appear to be inadequate for controlling sport doping, this letter recommends further research into conditional superannuation as a supplementary anti-doping policy to assist in safeguarding athlete health and welfare by lowering the incentive to utilize banned substances. The policy may also have applications to further domains of health including hospitals, allied health services, and aged care.